Soft porous crystals - Horike, Satoshi; Shimomura, Satoru; Kitagawa, Susumu (Nature chemistry, 2009)
Encapsulating guest molecules inside host structures ranging from soft, flexible enzymes to rigid, porous zeolites has led to developments in many areas, including catalysis, sensing and separation. This Review highlights how metal–organic frameworks — materials formed by linking metal centres with organic ligands — can combine softness with regularity to produce dynamic, yet crystalline, structures that may prove useful for a range of applications. The field of host–guest complexation is intensely attractive from diverse perspectives, including materials science, chemistry and biology. The uptake and encapsulation of guest species by host frameworks are being investigated for a wide variety of purposes, including separation and storage using zeolites, and recognition and sensing by enzymes in solution. Here we focus on the concept of the cooperative integration of 'softness' and 'regularity'. Recent developments on porous coordination polymers (or metal–organic frameworks) have provided the inherent properties that combine these features. Such soft porous crystals exhibit dynamic frameworks that are able to respond to external stimuli such as light, electric fields or the presence of particular species, but they are also crystalline and can change their channels reversibly while retaining high regularity. We discuss the relationship between the structures and properties of these materials in view of their practical applications.